The Association Between Initial Solid Food and Atopy in Children with or without Family History of Atopic Disease - Perdana, Nanan Surya; Setiabudiawan, Budi; Kartasasmita, Cissy B. (Majalah Kedokteran Bandung)
Atopic diseases are the most common chronic diseases in childhood. Their incidence has a tendency to increaseÂ recently. The tendency of atopy could be triggered by many factors originated in the early life, including earlyÂ introduction of solid food. To investigate the association between initial solid food and atopy, an analyticÂ comparative study with historical cohort design was conducted from May to June 2006 in Pediatric Department ofÂ Hasan Sadikin Hospital Bandung. It was the second phase study of 'allergic prevalence and risk factors identification in the first two years of life'. Out of 800 children in Garuda, Padasuka, and Babakansari Primary Health Care CenterÂ who were included in the first phase of the study, 749 children were eligible to continue the second phase of the study,Â 284 children were randomized into two groups of children with and without family history of atopic diseaseÂ consisting of 142 children each. They then underwent skin prick test. History of initiation time of solid food wereÂ obtained from their parents. To analyze the data chi-square and odds ratio with 95% confidence interval were used.Â Among 284 children who fullfilled the inclusion criteria, 50% had family history of atopic disease. Atopy was foundÂ in 28.2% children, 32.4% with family history of atopic disease and 23.9% without family history of atopic disease.Â There was no significant correlation between family history of atopic disease and atopy (p=0.113). There was a highÂ risk for atopy related to initial solid food (OR = 4.50, 95%CI = 1.96-10.74, p < 0.001). The difference of atopy wasÂ strongly significant between children who had initial solid food at the age of <6 months and at the age of >6 monthsÂ whether or not the children had family history of atopic disease (p=0.016 and p=0.002). Conclusions: A significantÂ increase in the risk of childhood atopy occured if initial solid food is given at the age of <6 months, whether or not theÂ children have family history of atopic disease.Hubungan antara Waktu Pemberian Makanan Pendamping ASIÂ dan Kejadian Atopi pada Anak dengan atau Tanpa Riwayat PenyakitÂ Atopik dalam KeluargaPenyakit atopik merupakan penyakit kronik yang paling sering ditemukan pada anak. Angka kejadian penyakitÂ atopik cenderung meningkat dari tahun ke tahun. Kecenderungan atopi atau timbulnya penyakit atopik dapatÂ dicetuskan oleh faktor faktor yang berpengaruh di awal kehidupan, salah satunya adalah pemberian makananÂ pendamping ASI (MP ASI). Untuk mengetahui hubungan antara waktu pemberian MP ASI dan kejadian atopiÂ dilakukan penelitian analitik komparatif dengan rancangan historical cohort. Penelitian dilakukan pada bulan Mei-Juni 2006 di Bagian Ilmu Kesehatan Anak Rumah Sakit Hasan Sadikin Bandung. Penelitian ini merupakan faseÂ kedua dari penelitian â€œPrevalens alergi dan identifikasi faktor risiko pada dua tahun pertama kehidupanâ€. PenelitianÂ dilakukan di Puskesmas Garuda, Padasuka, dan Babakansari. Dari 800 anak yang mengikuti fase I, sebanyak 749 anak dapat diteliti pada penelitian fase II. Dengan teknik sampling secara acak terpilih 142 anak, masing-masing dari Â kelompok dengan dan tanpa riwayat penyakit atopik dalam keluarga. Selanjutnya dilakukan pemeriksaan uji tusuk kulit dan ditanyakan mengenai riwayat pemberian MP ASI. Analisis statistik yang digunakan adalah uji kai-kuadrat dan Odds ratio dengan IK95%. Dua ratus delapan puluh empat anak memenuhi kriteria inklusi penelitian. Dari jumlah tersebut diperoleh 50% anak dengan riwayat penyakit atopik dalam keluarga. Atopi didapatkan pada 28,2% anak, 32,4% di antaranya dengan riwayat penyakit atopik dan 23,9% tanpa riwayat penyakit atopik dalam keluarga. Tidak terdapat hubungan yang bermakna antara anak dengan riwayat penyakit atopik dalam keluarga dan kejadian atopi (p=0,113). Dua ratus delapan (73,2%) anak mendapat MP ASI pada usia <6 bulan, 76 (26,8%) anak mendapat ASI pada usia >6 bulan. Kejadian atopi berbeda bermakna antara anak yang mendapat MP ASI pada usia <6 bulan dan >6 bulan (OR=4,50; IK95%=1,96-10,47; p<0,001), baik pada kelompok anak dengan riwayat penyakit atopik (OR=3,38; IK95%=1,12-10,86; p=0,016) maupun tanpa riwayat penyakit atopik (OR=6,08; IK95%=1,63-26,72, p=0,002) dalam keluarga. Kesimpulan: Pemberian MP ASI pada usia <6 bulan meningkatkan risiko terjadinya atopi, baik pada kelompok anak dengan atau tanpa riwayat penyakit atopik dalam keluarga.DOI:Â http://dx.doi.org/10.15395/mkb.v42n1.6Â